Development and Application of a Loop-Mediated Isothermal Amplification (LAMP) Approach for the Rapid Detection of Dirofilaria repens from Biological Samples. - Donato Antonio Raele; Nicola Pugliese; Domenico Galante; Laura Maria Latorre; Maria Assunta Cafiero (Public Library of Science (PLoS), 2016)
Dirofilariasis by Dirofilaria repens is an important mosquito vector borne parasitosis, and the dog represents the natural host and reservoir of the parasite. This filarial nematode can also induce disease in humans, and in the last decades an increasing number of cases have been being reported. The present study describes the first loop mediated isothermal amplification (LAMP) assay to detect D. repens DNA in blood and mosquitoes. Two versions of the technique have been developed and described: in the first, the amplification is followed point by point through a real time PCR instrument (ReT-LAMP); in the second, the amplification is visualized by checking UV fluorescence of the reaction mixture after addition of propidium iodide (PI-LAMP). The two variants use the same set of 4 primers targeting the D. repens cytochrome oxidase subunit I (COI) gene. To assess the specificity of the method, reactions were carried out by using DNA from the major zoonotic parasites of the family of Onchocercidae, and no amplification was observed. The lower limit of detection of the ReT-LAMP assay was 0.15 fg/μl (corresponding to about 50 copy of COI gene per μl). Results suggest that the described assay is specific, and its sensitivity is higher than the conventional PCR based on the same gene. It is also provide a rapid and cost-effective molecular detection of D. repens, mainly when PI-LAMP is applied, and it should be performed in areas where this emerging parasitosis is endemic.